On recursive hyperbolic functions in Fibonacci-Lucas sense - DAŞDEMİR, Ahmet; ŞENTÜRK, Tuncay Deniz; ÜNAL, Zafer (Hacettepe University, 2020)
The hyperbolic Fibonacci and hyperbolic Lucas functions have been introduced before and have been improved to functions of the symmetrical form. In this paper, we generalize the mentioned definitions, which will be called Horadam hyperbolic sine function $ \left( HSF \right) $ and Horadam hyperbolic cosine function $ \left( HCF \right) $. Further, we present many identities and hyperbolic properties of our new definitions.
Keywords: quasi-sine Horadam function; Matematik; Horadam spiral; Vajda's identity; Fibonacci and Lucas numbers and polynomials and generalizations; Honsberger formula; Horadam hyperbolic function; Horadam hyperbolic function; Horadam spiral; quasi-sine Horadam function; Honsberger formula; Vajda’s identity; Mathematical Sciences